Analisis Wacana Kritis Industri Media Netflix pada Film Dokumenter Ice Cold - Ummah, Syadathul; Hidayat, Dasrun (Ideas Publishing, 2024)
This research is motivated by the number of people who immediately accept the information conveyed in the movie Ice Cold, forgetting that Netflix is a media industry that regulates profit. The purpose of this research is to analyze a discourse by measuring the levels of subjectivity and objectivity. Qualitative research method with the theory used van Dijk’s critical discourse analysis model. The results found that Netflix as a media owner can set movie scenarios to meet the needs of capitalists who regulate political economic interests by creating a construction of reality in this film. The implication of this research is expected to make people care about the construction of media discourse and be smart in considering various empirical facts